Language and Identity in the Digital Age: Discourse Analysis of Online Communities Based on Regional Languages - Evizariza, Evizariza; Na, Li; Wei, Sun (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Humans are social creatures who cannot live alone. This requires a language that unites one individual with another, group with group, or individual with group. Language is an important component in a person's identity. Language is not only a means of communication, delivering messages, or even jokes. The influence of digital can create online communication. The purpose of this study is to find out how regional languages are used in online communities that affect the identity of their users. Through an analytical approach and literature study, researchers collected information from various journals or related articles. The results of the study show that regional languages can strengthen the identity of a region and its individuals. In addition, it also creates space for social solidarity and strengthening language communities. The results of this study in the form of a community of regional languages will revive regional languages that have faded. The existence of a new spirit in creativity in developing regional languages as local cultures will be able to reduce the rate of extinction of regional languages. Many regions have reused regional languages as everyday languages and are combined in learning. The conclusion of this study, a strong desire is needed to increase the protection of diverse cultures in Indonesia. 700 languages that must continue to be pursued in cultural defense. We need a young generation that is not embarrassed to use regional languages in everyday life.